Investigating the Effects and Side Effects of Two Antipsychotic Drugs in the Treatment of Children and Adolescents with Tourette Syndrome: A Semi-experimental Research - Soltanifar, Atefeh; Lashkarnevis, Raheleh; Ziaee, Maliheh; Moharari, Fatemeh; Samadi, Roya; Soltanifar, Azadeh; Kamrani, Maedeh (Current Drug Discovery Technologies, 2023)
Introduction: Due to the high prevalence of Tourette's disorder among children and adolescents and its negative consequences, an appropriate and effective medical treatment with minimal complications is necessary. Therefore, this study was conducted to compare the effects of Aripiprazole and Risperidone on Tourette's disorders in children and adolescents. Methods: The statistical population of this semi-experimental study was children and adolescents aged seven to eighteen years old. They were diagnosed with Tourette's disorder based on the DSM-V criteria by the clinical interview of a child and adolescent psychiatrist in the child Psychiatry clinic of Ibne- Sina's Psychiatric Hospital (Mashhad-Iran) in 2018. A total of forty participants were selected by the convenience sampling method, and they were randomly divided into two groups treated with medicines, Risperidone or Aripiprazole, for two months. Then, the demographic information questionnaire was completed. The Y-GTSS Scale was completed. The clinical Effect Rating Scale (CGI-Tics Scale) was completed. Calculation of body mass index and medical side effects complications were completed. The evaluation was carried out at the beginning and on the second, fourth, and eighth weeks, and the results were compared. The data were analyzed using SPSS software. 14, descriptive statistics, Chi-square, and variance analysis. Results: The two groups were homogeneous in terms of demographic variables and body mass index. Despite the positive effect of both medicines, no significant difference was observed among the general scores of such disorders, the overall score of severity, Tourette's recovery, and BMI of these two groups at the intervals and the end of treatments. (p <0.05). Due to the low number of complications reported, statistical comparisons of the medical side effects were not made. Conclusion: According to the results, the two medicines, Aripiprazole and Risperidone, effectively improved the symptoms of Tourette's disorder and its overall severity. However, there were no significant statistical differences between them. Furthermore, in terms of the medical side effects, the statistical comparison between the two medicines was impossible due to the small number of complications.
Keywords: tourette' s syndrome